2022
DOI: 10.1177/03635465221118375
|View full text |Cite|
|
Sign up to set email alerts
|

Recall Bias in the Retrospective Collection of Common Patient-Reported Outcome Scores in Hip Arthroscopy

Abstract: Background: The use of patient-reported outcomes (PROs) is common practice in the treatment of patients undergoing hip arthroscopy. While the prospective collection of PROs is preferred, retrospective collection involving patient recall is not uncommon and may be subject to bias. Purpose: To assess the presence of recall bias between prospectively and retrospectively collected PRO scores in hip arthroscopy. Study Design: Cohort study; Level of evidence, 2. Methods: Patients who underwent hip arthroscopy betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We are confident that achieving this will lead to a better understanding of recall biases. Interestingly, in addition to interval of time, which is a well-known key factor affecting recall bias, different cough trajectories, which were not considered in previous studies, [26][27][28]40 are also important culprits leading to different recall biases. Therefore, in practice, when retrospective assessment is performed, different measurements should be taken according to the patient's specific situation to prevent the occurrence of different recall biases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We are confident that achieving this will lead to a better understanding of recall biases. Interestingly, in addition to interval of time, which is a well-known key factor affecting recall bias, different cough trajectories, which were not considered in previous studies, [26][27][28]40 are also important culprits leading to different recall biases. Therefore, in practice, when retrospective assessment is performed, different measurements should be taken according to the patient's specific situation to prevent the occurrence of different recall biases.…”
Section: Discussionmentioning
confidence: 91%
“…These studies showed that retrospective assessments overestimate the actual status of patients. 26,40 This disparity may be related to the differences in the research design. We used longitudinal data as the research goal to analyze recall bias more comprehensively; a great advantage of the longitudinal design is that we found that patients with lung cancer had different cough trajectories after discharge, which is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, our mean follow-up duration was 2 6 1 years. Prior studies demonstrate that recall bias is not as much of an issue when less time has elapsed since surgery [5,21], and we believe the time frame we used here was short enough that patients were likely to remember how they felt before and after surgery. Additionally, some patients declined to participate in the study.…”
Section: Limitationsmentioning
confidence: 99%
“…It is common that the athletes report on their level of sports before onset of symptoms, which might have been years ago, which is further problematized with the risk of recall bias. 4,26 RTS is considered essential in the decision of how to treat sports injuries and is also the biggest concern for caregivers to give proper expectations to athletic patients. Accurate measurements of level of sports and RTS are therefore important to examine.…”
mentioning
confidence: 99%
“…It is common that the athletes report on their level of sports before onset of symptoms, which might have been years ago, which is further problematized with the risk of recall bias. 4,26…”
mentioning
confidence: 99%